Composition models for augmented instruments: HASGS as case study - Portovedo, Henrique (2022)
This paper presents the concept of HASGS regarding the augmentation procedures applied to an acoustic instrument, at the same time that it is analyzed how composers applied technology prototyped to the composition of works. The development of HASGS has been driven by the compositional aspects of the original music created for this specific electronic augmented instrumental system. Instruments are characterized not only by their sound and acoustical properties but also by their performative interface and evolutionary repertoire. This last aspect has the potential to establish a practice among performers at the same time as creating the ideal of community contributing to the past, present and future of that instrument. Augmenting an acoustic instrument places some limitations on the designer ́s palette of feasible gestures because of those intrinsic performance gestures, and the existing mechanical interface, which have been developed over years, sometimes, centuries of acoustic practice. We conclude that acoustic instruments and digital technology, are able to influence and interact mutually creating Augmented Musical Performance environments based on the aesthetics of the repertoire being developed. This work is, as well, a resource of compositional methods to composers and programmers.